Artificial Salmonella vaccines: O-antigenic oligosaccharide-protein conjugates induce protection against infection with Salmonella typhimurium. - Svenson, S B (1979)
Outbred mice were vaccinated with various artificial Salmonella vaccines and subsequently challenged intraperitoneally with graded doses of virulent Salmonella typhimurium. The Salmonella vaccines used were: (i) octasaccharide, obtained by hydrolysis of the O-antigenic polysaccharide chain of S. typhimurium strain SH 4809 with phage P22-associated endo-rhamnosidase and covalently linked to either diphtheria toxin or edestine; (ii) purified outer membrane proteins (porins) from S. typhimurium; and (iii) octasaccharide covalently linked to porins. All vaccines induced significant protection against experimental infection of mice with S. typhimurium. However, vaccination with the octasaccharide-porin conjugate resulted in better protection than that obtained by vaccination with octasaccharide or porin vaccines separately. Rabbit antibodies raised against the different vaccines were also passively administered intravenously to mice. Such mice were protected against challenge with virulent S. typhimurium by antibodies specific for the S. typhimurium O-antigen or for the porins. Thus, active immunization with more than one surface component of Salmonella bacteria improved the efficacy of the vaccine. The data from the passive immunization experiments also emphasized the role of humoral immunity for protection against S. typhimurium infection.